Impact of Malawi’s Farm Income Diversification Programme on household welfare: Empirical evidence from eleven districts - Chirwa, Cuthbert Wadonda; Makoka, Donald; Maonga, Beston B.; Ng’ong’ola, Davies H. (International Food Policy Research Institute, 2017)
This study used cross sectional data from the government of Malawi’s Farm Income Diversification Programme (FIDP) to examine the impact of FIDP on household welfare. Total annual household income, food security, and the wealth status of households were used as measures of household welfare. A propensity score matching procedure was used to make statistically valid comparisons between the welfare of households which participated and did not participate in FIDP. The results show that households which participated in FIDP had higher incomes and their food security status improved more than among similar households which did not participate in the program. The results further reveal that FIDP improved the wealth of participating households compared to their counterparts who did not participate. Those FIDP participating households engaged in livestock production, in particular, experienced considerable growth of income, which suggests that livestock enterprises coupled with income from crops could be an important pathway for improving the wellbeing of households in Malawi.